(untitled) (Acta Scientiarum. Health Sciences, 2011)
The presence of ants in hospitals is health risk for the hospital community, since presents a strong capability to carry pathogenic organisms throughout this environment. This study was carried out from May 2007 to April 2008, aiming the identification of ant species that infest the hospitals in Porto Alegre, Rio Grande do Sul State, Brazil. A total of 989 ants from 19 species were sampled: Acromyrmex niger (Fr. Smith, 1858), Brachymyrmex sp., Camponotus rufipes (Fabricius, 1775), Camponotus sericeiventris (Guerin-Meneville, 1838), Camponotus sp1, Camponotus sp2, Gnamptogenys sp., Hypoponera sp., Labidus coecus (Latreille, 1802), Monomorium pharaonis (Linnaeus, 1758), Pachycondyla sp., Paratrechina fulva (Mayr, 1862), Paratrechina longicornis Latreille, 1802, Pheidole sp1, Pheidole sp2, Pheidole sp3, Pheidole sp4, Pheidole sp5, and Tapinoma melanocephalum Fabricius, 1793. Among them, Brachymyrmex sp. was the most frequent one (47.0%) followed by Monomorium pharaonis (18.7%) and Labidus coecus (17.2%).